Modelling and analysing the information processing capabilities of simple biological systems - Moskon, Miha; Mraz, Miha (Mathematical Modelling and Analysis, 2012)
Biological systems that present basic logic primitives for information processing have already been realized. Models for simulating their dynamics have also been implemented. However there is a lack of metrics that would objectively evaluate the information processing capabilities of these primitives and possibilities of their interconnectivity. With the introduction of such processing and performance descriptive quantities complex biological systems capable of information processing could be built more straightforwardly. That would bring us closer to the realization of a biological computer.